Quantification of optimal target reliability for seismic design: Methodology and application to steel buildings. Issue 170 (July 2023) - Habibi, Kasra; Hosseini Varzandeh, S. Saeid; Mahsuli, Mojtaba
Abstract: The reliability levels against which seismic standards are calibrated are currently quantified based on accepted practice, which may not lead to optimal designs that minimize the lifecycle cost. Deviation from optimal design is even more pronounced in countries whose regulations are adopted from the few leading codes. A major challenge in the quantification of optimal target reliability for the countries with such adopted codes is the lack of risk models that are suited for the local construction industry and design practices. This paper presents a holistic risk-based framework to quantify the optimal target reliability for seismic design through the notion of minimum lifecycle cost. To enable the implementation of the framework in countries with adopted provisions, the present paper proposes an approach to adapt the available risk models to the local conditions of those countries. The proposed framework is showcased through the National Building Code of Iran, which is adopted from the codes of the United States, using a case study of five residential steel building archetypes. The archetypes have various structural systems and comprise intermediate moment-resisting frame (IMF) buildings of various heights and special concentrically braced frame (SCBF) buildings. The results reveal 50-year optimal target reliability indices of 2.5, 2.0, and 1.9 for low-, mid-, and high-rise IMF buildings and 2.1 for mid-rise SCBF buildings. Highlights: Design codes that are adopted with no recalibration suffer from a lack of adequate safety. Quantifying target reliability for such codes is challenged by lack of risk models suited for local conditions. A framework is presented that tailors available risk models to the local industry and practices. It is applied to the building code of Iran using a case study of three building archetypes. The framework is readily applicable to building codes with adopted regulations.